Editing with archive footage - Flores, Virginia Osorio (Farol, 2024)
Audiovisual editing is, without a doubt, one of the most specific procedures in cinema. Not only in cinema, but in other visual art devices in general. In finished works, the forms of sequence, selection objectives and organizational principles of the image and sound materials say a lot about the subject of the discourse. Films made in Latin America are of particular interest to us and, for this study, we chose “Baile perfumado” (1997), by Lírio Ferreira and Paulo Caldas, “La última huella” (2001), by Paola Castillo, “A paixão de JL” (2015), by Carlos Nader, and “EAMI” (2022), by Paz Encina. The objective is to study and present one of the possible audiovisual editing regimes to observe how the chosen archive footage works intertwined with the materials produced by its authors. We will call this editing regime “editing with archive footage”.